1996
DOI: 10.1073/pnas.93.4.1412
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus chimeras replicating under the translational control of genetic elements of hepatitis C virus reveal unusual properties of the internal ribosomal entry site of hepatitis C virus.

Abstract: Chimeric genomes of poliovirus (PV) have been constructed in which the cognate internal ribosomal entry site (IRES) element was replaced by genetic elements of hepatitis C virus (HCV). Replacement of PV IRES with nt 9-332 of the genotype lb HCV genome, a sequence comprising all but the first eight residues of the 5' nontranslated region (5'NTR) of HCV, resulted in a lethal phenotype. Addition of 366 nt of the HCV core-encoding sequence downstream of the HCV 5'NTR yielded a viable PV/HCV chimera, which expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 38 publications
(33 reference statements)
3
145
3
Order By: Relevance
“…The three-stemmed appearance of negatively stained HCV IRES transcripts is in good agreement with the predicted model+ It is likely that the three domains visualized represent domains II-IV of the predicted model+ Although domain I is included in the construct, it is unlikely that the single-stranded RNA and the very small loop that forms domain I would be seen at the resolution achieved+ The extended nature of the RNA domains correlates with the results of small angle X-ray scattering (Kieft et al+, 1999), which suggests that the HCV IRES does not form a globular structure+ The length of the largest feature, domain III, was estimated by assuming that double-stranded regions of the IRES would adopt A form helices with a 2+73-Å rise per base pair and a 25-Å rise for each laterally protruding double helical subdomain+ Using these criteria, domain III was predicted to be .16 nm in length+ However, the presence of bulges and loops makes accurate prediction of the length of the proposed domain impossible+ The 18-nm stem (stem a) seen in the EM images is compatible with domain III+ The second stem (stem b) is 10 nm in length+ This fits well with domain II, which was predicted to be at least 7 nm in length+ The angles between stems a and b (putative domains III and II) suggests some flexibility, the angle ranging between 708 and 1308 with a mean at 958+ A small segment of non-base paired nucleotides in the region joining the stems is likely to be responsible for this ability to rotate+ It is worth pointing out that the wide range of angles seen between domains II and III is not a result of varying three-dimensional orientations of the molecules because "out of plane" stems would not be visualized by the negative staining technique+ This is in contrast to a study of the Tetrahymena group I intron ribozyme by Nakamura et al+ (1995) that employed a rotary shadowing technique that does impart contrast to distal segments of a stem that protrudes We have refined the model of the HCV IRES structure based on possible arrangements of domains II and III (Fig+ 7)+ Flexibility may be necessary for interaction of domain III with proteins involved in initiation of translation+ Although a recent study shows that subunits of eIF3 can bind to domain III in isolation (Buratti et al+, 1998), binding of the ribosomal protein S9 of the 40s ribosomal subunit requires the correct orientation of domains IIa, IIc, and IIId (Oldreman-Macchioli et al+, 2000)+ Thus movement of domain II relative to domain III may be prerequisite for binding of the 40s ribosomal subunit or subsequent events in HCV IRESmediated initiation of translation+ Unfortunately, the small size of the predicted apical loop of domain II precludes the use of oligonucleotides for further characterization of this region of the IRES+ The shortest stem (stem c) seen on the particles is 2 nm long and probably corresponds to domain IV+ This region is adjacent to the pseudoknot and the putative ribosomal-binding site+ The exact role of this stem in translation initiation is unclear as several studies demonstrate that disruption of the stem loop that forms domain IV has little effect on the efficiency of translation (Tsukiyama-Kohara et al+, 1992; Wang et al+, 1993)+ In contrast, certain reporter constructs in which the base pairing of this stem has been disturbed show a marked decrease in expression of the reporter protein (Reynolds et al+, 1995;Honda et al+, 1996;Lu & Wimmer, 1996)+ In the latter case, the reporter gene sequence may interact with and disrupt upstream secondary and tertiary RNA structures, thereby altering the conformation of the IRES+ It is...…”
Section: Discussionmentioning
confidence: 99%
“…The three-stemmed appearance of negatively stained HCV IRES transcripts is in good agreement with the predicted model+ It is likely that the three domains visualized represent domains II-IV of the predicted model+ Although domain I is included in the construct, it is unlikely that the single-stranded RNA and the very small loop that forms domain I would be seen at the resolution achieved+ The extended nature of the RNA domains correlates with the results of small angle X-ray scattering (Kieft et al+, 1999), which suggests that the HCV IRES does not form a globular structure+ The length of the largest feature, domain III, was estimated by assuming that double-stranded regions of the IRES would adopt A form helices with a 2+73-Å rise per base pair and a 25-Å rise for each laterally protruding double helical subdomain+ Using these criteria, domain III was predicted to be .16 nm in length+ However, the presence of bulges and loops makes accurate prediction of the length of the proposed domain impossible+ The 18-nm stem (stem a) seen in the EM images is compatible with domain III+ The second stem (stem b) is 10 nm in length+ This fits well with domain II, which was predicted to be at least 7 nm in length+ The angles between stems a and b (putative domains III and II) suggests some flexibility, the angle ranging between 708 and 1308 with a mean at 958+ A small segment of non-base paired nucleotides in the region joining the stems is likely to be responsible for this ability to rotate+ It is worth pointing out that the wide range of angles seen between domains II and III is not a result of varying three-dimensional orientations of the molecules because "out of plane" stems would not be visualized by the negative staining technique+ This is in contrast to a study of the Tetrahymena group I intron ribozyme by Nakamura et al+ (1995) that employed a rotary shadowing technique that does impart contrast to distal segments of a stem that protrudes We have refined the model of the HCV IRES structure based on possible arrangements of domains II and III (Fig+ 7)+ Flexibility may be necessary for interaction of domain III with proteins involved in initiation of translation+ Although a recent study shows that subunits of eIF3 can bind to domain III in isolation (Buratti et al+, 1998), binding of the ribosomal protein S9 of the 40s ribosomal subunit requires the correct orientation of domains IIa, IIc, and IIId (Oldreman-Macchioli et al+, 2000)+ Thus movement of domain II relative to domain III may be prerequisite for binding of the 40s ribosomal subunit or subsequent events in HCV IRESmediated initiation of translation+ Unfortunately, the small size of the predicted apical loop of domain II precludes the use of oligonucleotides for further characterization of this region of the IRES+ The shortest stem (stem c) seen on the particles is 2 nm long and probably corresponds to domain IV+ This region is adjacent to the pseudoknot and the putative ribosomal-binding site+ The exact role of this stem in translation initiation is unclear as several studies demonstrate that disruption of the stem loop that forms domain IV has little effect on the efficiency of translation (Tsukiyama-Kohara et al+, 1992; Wang et al+, 1993)+ In contrast, certain reporter constructs in which the base pairing of this stem has been disturbed show a marked decrease in expression of the reporter protein (Reynolds et al+, 1995;Honda et al+, 1996;Lu & Wimmer, 1996)+ In the latter case, the reporter gene sequence may interact with and disrupt upstream secondary and tertiary RNA structures, thereby altering the conformation of the IRES+ It is...…”
Section: Discussionmentioning
confidence: 99%
“…The observation that binary complexes yielded toeprints downstream of HCV and CSFV initiation codons indicate that the coding regions of both RNAs are fixed stably in the mRNA-binding cleft of 40S subunits. This observation may also provide an explanation for the importance of the conserved sequences adjacent to the initiation codon for IRES function (Reynolds et al 1995;Honda et al 1996;Lu and Wimmer 1996).…”
Section: Binary Ires-40s Subunit Complexes Arrest Primer Extension Wimentioning
confidence: 99%
“…Ribosomal entry also occurs at or immediately upstream of the initiation codon on HCV-like IRESs and initiation probably also does not involve scanning (Reynolds et al 1995(Reynolds et al , 1996Rijnbrand et al 1995Rijnbrand et al , 1996Rijnbrand et al , 1997Wang et al 1995;Honda et al 1996;Lu and Wimmer 1996). Several properties, however, distinguish HCV-like IRESs from EMCV-like IRESs.…”
mentioning
confidence: 99%
“…Hepatitis C virus (HCV), a plus sense RNA virus identified in 1989 (Choo et al+, 1989), is estimated to chronically infect roughly 4,000,000 people in the United States (National Institutes of Health, 1997), often with serious consequences (for a review, see Branch et al+, 2000)+ Because HCV poses a public health threat, it is important to identify all HCV RNA structural elements and expressed polypeptides to define all potential diagnostic markers, vaccine components, and targets for pharmaceutical agents+ At the moment, HCV RNA is known to contain a single large open reading frame (ORF), about 9,000 nt in length, encoding a single polyprotein that is the source of 10 viral proteins: the core, E1, E2, P7, NS2, NS3, NS4a, NS4b, NS5a, and NS5b (Rice, 1996)+ This ORF is flanked by about 350 nt at its 59 end and about 220 at its 39 end+ Although the full range of the functions provided by the flanking sequences is not yet clear, terminal structures are likely to play a role in replication, and the 59 flanking sequence forms part of an internal ribosome entry site (IRES) that promotes the initiation of HCV polyprotein synthesis (Brown et al+, 1992;Tsukiyama-Kohara et al+, 1992;Reynolds et al+, 1995;Lu & Wimmer, 1996)+ As exemplified by the hepatitis B virus, viral genomes often contain overlapping genes+ Thus, HCV RNA may contain regions where the main ORF is overlapped by another gene or by an RNA structural element+ To seek these multifunctional regions, we carried out comparative sequence analysis on diverse HCV sequences retrieved from GenBank (Benson et al+, 1996), locating synonymous codons in the standard HCV ORF in which the third position nucleotides are much more conserved than chance alone would pre-dict+ This unusual third-base conservation is likely to occur in regions that have novel functions in addition to their known coding function (see Materials and Methods)+ Previous studies identified some of the regions of HCV RNA that have unusual nucleotide conservation (Ina et al+, 1994;Smith & Simmonds, 1997) and, in particular, they revealed that the RNA sequence of the core-encoding region is more conserved than would be necessary to maintain the observed level of conservation of the core protein+ Ina and colleagues (Ina et al+, 1994) suggested that an overlapping gene might constrain the sequence and proposed that translation of a second ORF might be initiated at the GUG codon at bases Ϫ41 to Ϫ39 and continue into the coding region+ However, the reading frame that contains this GUG has an in-frame stop codon (bases ϩ2 to ϩ4) that terminates it at the start of the main ORF+ This stop codon is present in all reported full-length core sequences; its presence reduces the likelihood that the GUG functions as the start codon for a protein that extends into the core-encoding region+ Smith and Simmonds (1997) concluded that the reduced frequency of synonymous substitutions "cannot be accounted for by additional coding restraints" (p+ 240)+ Recent studies indicate that the initial segment of the core-encoding region of the main HCV ORF contains features necessary for th...…”
Section: Introductionmentioning
confidence: 99%